Peran Transformational Leadership dan Job Satisfaction Terhadap Intention to Stay dengan Job Engagement sebagai Mediasi pada Karyawan PT XYZ [The Role of Transformational Leadership and Job Satisfaction on Intention to Stay with Job Engagement as Mediation for PT XYZ Employees] - Heren, Langisa; Ong, Daniel (Universitas Pelita Harapan, 2023)
This research was conducted to determine the role of Transformational Leadership and Job Satisfaction on Intention to Stay with Job Engagement as Mediation for PT XYZ Employees. The high sense of intention to stay for PT XYZ employees to carry out their responsibilities as employees is influenced by the transformational leadership style, job satisfaction and job engagement. The research was carried out using quantitative research methods, with a judgment sampling technique in which respondents had to meet predetermined requirements as research respondents. Respondents in this study amounted to 130 respondents. The data collection technique uses a research instrument in the form of a questionnaire with a Likert scale of 1–5. The data obtained was then analyzed and processed using the Structural Equation Model (SEM) technique with SmartPLS 4.0 Software. Based on the research conducted, it can be concluded that transformational leadership has a positive effect on job engagement, job satisfaction has a positive effect on job engagement, transformational leadership has a positive effect on intention to stay mediated by job engagement, and job satisfaction has a positive effect on intention to stay mediated by job engagement. This research has benefits for companies in being able to maintain and improve transformational leadership, job satisfaction, and job engagement in order to increase employees' intention to stay, as well as become a reference for further research.Bahasa Indonesia Abstrak: Penelitian ini dilakukan untuk mengetahui peran transformational leadership dan job satisfaction terhadap intention to stay dengan job engagement sebagai mediasi pada Karyawan PT XYZ. Tingginya rasa intention to stay pada karyawan PT XYZ untuk tetap melakukan tanggung jawabnya sebagai karyawan dipengaruhi oleh gaya kepemimpinan transformational leadership, job satisfaction dan job engagement. Penelitian dilakukan dengan metode penelitian kuantitatif, dengan teknik judgment sampling di mana responden harus memenuhi syarat yang telah ditentukan sebagai responden penelitian. Responden dalam penelitian ini berjumlah 130 responden. Teknik pengumpulan data menggunakan instrumen penelitian berupa kuesioner dengan skala Likert 1–5. Data yang diperoleh kemudian dianalisis dan dilakukan pengolahan menggunakan teknik Structural Equation Model (SEM) dengan Software SmartPLS 4.0 Berdasarkan penelitian yang dilakukan, dapat disimpulkan bahwa transformational leadership berpengaruh positif terhadap job engagement, job satisfaction berpengaruh positif terhadap job engagement, transformational leadership berpengaruh positif terhadap intention to stay yang dimediasi oleh job engagement, dan job satisfaction berpengaruh positif terhadap intention to stay yang dimediasi oleh job engagement. Penelitian ini memiliki manfaat bagi perusahaan untuk dapat mempertahankan dan meningkatkan gaya kepemimpinan transformational leadership, job satisfaction, dan job engagement guna meningkatkan rasa intention to stay pada karyawan, serta menjadi referensi untuk penelitian selanjutnya.